Olympic Games Rio 2016: The Legacy for Coaches - Padrão dos Santos Ana Lúcia (Sciendo, 2019)
The purpose of this study is to identify the legacy of the Olympic Games for sports coaches with a special focus on professional education. Thus, in framing this study, two research questions are posed: 1) How did Olympic Games affect the characteristics of the educational activities for coaches? 2) What was the perception about the coaches' education in Brazil, and the legacy of the event for coach's education and career? The methodology used was the content analysis of the websites of National Sports Confederations, Institutions of Higher Education in the State of Rio de Janeiro, and the National and Regional Professional Councils in Brazil, totaling 70 institutions. Concomitantly, interviews were conducted with members of the Ministry of Sport, the Brazilian Olympic Academy, and the Federal Council of Physical Education. The interview questions were grounded on the theoretical framework of Sports Policy Factors Leading To International Sporting Success - SPLISS, which included: 1) the existence of well-trained and experience elite coaches in the country; 2) opportunities to develop their coaching career to become a world-class elite coach; 3) the status of coaches and the recognition of their work as valuable throughout the country. The results indicated that the event brought few benefits to coaches. In addition, according to the interviews, coaches play a secondary role in the organization of the Olympic Games, although they are considered fundamental for the development of the sport. Based on the results, this study discusses the education of coaches and the perceived importance of coaches according to the sports and educational institutions.